Central limit theorem for special classes of functions of ergodic chains - Moskal'tsova, N. V.; Shurenkov, V. M.; Москальцова, Н. В.; Шуренков, В. М.; Москальцова, Н. В.; Шуренков, В. М. (Institute of Mathematics, NAS of Ukraine, 1994)
A central limit theorem is proved for E-finite bounded functions of ergodic Markov chains. Two useful corollaries are presented.